The Effect of Balanced Scorecard on the Private College Performance (Case Study at the University of WR Supratman Surabaya) - Gamal, Ahmad; Soemantri, Asep Iwa (Archives of Business Research, 2017)
One important factor that is used to assess the success of private college is performance. Private colleges continue their efforts to prepare and fine-tune their business strategies in order to survive in the world of education and even become a winner in the competition. Measurement of performance becomes a very important thing. Balanced Scorecard has goal and measurement that is not only a combination of financial and non-financial measurement, but is the result of a top-down process based on the mission and strategy of a private college. The purpose of this study is to determine the effect of Balanced Scorecard model toward performance of future private colleges. The independent variable in this study is the Balanced Scorecard that consists of customer perspective, financial perspective, internal business process perspective and the perspective of process of growth and learning, while the dependent variable is the performance of the private college (Y). The sample in this study is 100 people covering over half of the students (IV and above) who are active students at the University of WR Supratman Surabaya. Method of data processing is using multiple linear regression with SPSS. The result of Discussion can be concluded that (1) Balanced scorecard model simultaneously effects on the performance of future private colleges significantly, which is characterized by the significant value of F arithmetic amounted to 0.000 (0.000 <0.05), and (2) Balanced scorecard model partially influences to the performance of the future private colleges significantly, which is marked with significant value of t calculate of customer perspective amounted 0.014 (0.014 <0.05), the customer's financial perspective for 0.035 (0.035 <0.05), internal business process perspective of 0.002 (0.002 < 0.05) and the perspective of growth and learning process of 0.000 (0.000 <0.05)